Analisis Perbandingan Persepsi Konsumen Mengenai Store Atmosphere Pada Ritel Modern Dan Ritel Konvensional (Studi Kasus Pada Indomaret Dan Toko Dedy Di Tenggarong) - Silvia Nurma Novianti; Awang Yacoub Luthman; Ilham Ilham (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract:Our highly perceived form of word is the distance that reads these small traders fret. If retail business grows year by year in the absence of prevailing regulations then it is with conventional market which will also reduce revenue from the conventional market itself, because the adjacent distance is certainly cheaper than traditional market. The purpose of this research is to know and analyze comparison of consumer perception about store atmosphere in modern retail (Indomaret) and conventional retail (Toko Dedy). The data used is primary data. This research method using purposive sampling, with the terms and conditions applicable. Samples studied were 91 respondents. Number of variables studied is 1 ie store atmosphere with 4 indicators. In this research using Paired Sample T-Test analysis by comparing the average value in modern retail (Indomaret) and conventional retail (Toko Dedy). From the results of the study stated that the first hypothesis statement in this study which states "that there are significant differences in consumer perceptions of store atmosphere in modern retail and conventional retail" received. This is reinforced by the result of Paired Sample T-Test obtained by tcount equal to 37,919 which is bigger than ttable that is 1,9867 with probability (Sig.) 0.000 which is also smaller than 0,05. Then a statement from the second hypothesis stating that "the difference in consumer perception of store atmosphere in modern retail is more dominant than conventional retail" is accepted. It is proved by comparison result of mean value of Paired Sample Statistics obtained by mean value in modern retail (indomaret) equal to 58,5275 while mean value in conventional retail (Toko Dedy) is smaller that is equal to 29,7692. Keywords: Store Atmosphere, Modern Retail, Conventional Retail.